Effect of intensive blood pressure lowering on cardiovascular outcomes based on cardiovascular risk: A secondary analysis of the SPRINT trial. (February 2019) - Attar, Armin; Sayadi, Mehrab; Jannati, Mansoor
Background: It is not clear whether risk stratification can help choose the most favourable systolic blood pressure target for primary prevention of cardiovascular events. Design: A secondary analysis of Systolic Blood Pressure Intervention Trial (SPRINT). Methods: To perform a secondary analysis, we obtained the data from SPRINT from the National Heart, Lung, and Blood Institute data repository centre. In SPRINT, an open-label trial, participants without diabetes with systolic blood pressure of ≥130 mmHg were randomly assigned to intensive and standard treatment groups with systolic blood pressure targets of <120 and <140 mmHg, respectively. The primary composite outcome was myocardial infarction and other acute coronary syndromes, stroke, heart failure, or death from cardiovascular causes. Here, we have analysed data from participants without cardiovascular disease and chronic kidney disease aged under 75 years categorised based on the baseline 10-year Framingham risk score (<10% (low risk); ≥10% and <15% (intermediate risk); ≥15% (high risk)). Results: A total of 4298 patients were included in the analysis. With intensive treatment, there was a significant reduction in the primary outcome events in patients at high risk (0.86% per year vs. 1.81% per year; hazard ratio (HR) 0.51; 95% confidence interval (CI) 0.31 to 0.85; P = 0.010), and at intermediate risk (0.60% per year vs. 1.46% per year; HR 0.37; 95% CI 0.17 to 0.82; P = 0.014) but not for those at low risk (0.75% per year vs. 0.57% per year; HR 1.14; 95% CI 0.55 to 2.38; P = 0.714). Conclusions: Intensive systolic blood pressure reduction is beneficial for primary prevention of cardiovascular morbidity and mortality in patients without diabetes with more than low cardiac risk (above 10%).